The Critical Value Chain: A Narrative Review of Systems Analysis, Human Factors, and Security-Based Interventions to Prevent Communication Failures in Life-Threatening Laboratory Result Reporting - Mahdi, Yahya Hamad Ahmed; Lamyaa Mahdi Mohammed Hazazi; Elham Ali A Mahnashi; Mohammed Ibrahim Mohsen Gome; Abdullah Essa Magbool Oraybi; Khalid Hamoud Najea Somaily; Ahlam Mohammed Ahmed Arishi; Essa Ali Ali Oraybi; Abdullah Zain Abdullah Abbas; Samira Ali Hussin Halawi; Amani Mohammed Ali Arishi; Huda Ali Hassan Alshehri; et al. (Saudi Journal of Medicine and Public Health, 2024)
<span style="font-size: 12pt; font-family: Calibri, sans-serif; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Calibri, sans-serif; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The timely and reliable communication of critical laboratory values (CLVs)—results indicating imminent, life-threatening patient risk—is a non-negotiable patient safety standard. Despite long-standing protocols, failures in this communication chain persist, leading to diagnostic and treatment delays, patient harm, and sentinel events. These failures represent systemic vulnerabilities rather than isolated human errors. <span style="font-size: 12pt; font-family: Calibri, sans-serif; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Calibri, sans-serif; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This narrative review aims to analyze the multi-factorial causes of CLV communication breakdowns and synthesize evidence for a systems-based, security-informed response. It specifically evaluates the integrated roles of the clinical laboratory, nursing, and healthcare security/patient safety functions in designing fail-safe processes. <span style="font-size: 12pt; font-family: Calibri, sans-serif; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Calibri, sans-serif; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> An integrative narrative review methodology was employed. A systematic search of PubMed, CINAHL, Scopus, and Web of Science (2010-2024) was conducted. Keywords included "critical results," "critical values," "communication failure," "patient safety," "laboratory reporting," and "systems analysis." Included literature comprised sentinel event reports, root cause analyses, quality improvement studies, and reviews on health information technology and human factors engineering. <span style="font-size: 12pt; font-family: Calibri, sans-serif; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Calibri, sans-serif; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Communication failures arise from a complex interplay of latent system conditions (e.g., poorly designed interfaces, ambiguous policies, alert fatigue) and active errors (e.g., misdialed numbers, unacknowledged alerts). Effective mitigation requires a multi-layered defense: 1) Robust, redundant, and secure technological pathways mandated and audited by Health Care Security; 2) Clear, standardized protocols defining laboratory and nursing duties with closed-loop verification; 3) A proactive security mindset that treats failures as system breaches, necessitating rigorous root cause analysis and the implementation of corrective controls (e.g., read-back protocols, automated escalation, system hardening). <span style="font-size: 12pt; font-family: Calibri, sans-serif; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Calibri, sans-serif; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Safeguarding the critical value chain demands reconceptualizing it as a vital security protocol within the clinical environment. Moving beyond policy reiteration to engineered reliability, informed by human factors and security principles, is essential. A collaborative model where laboratory science, nursing practice, and security engineering jointly own the integrity of this high-stakes information pathway is paramount for eliminating preventable harm.